Province- and Individual-Level Influential Factors of Depression: Multilevel Cross-Provinces Comparison in China - Gou, Yue; Wu, Nianwei; Xia, Jing; Liu, Yanjun; Yang, Huawu; Wang, Haibo; Yan, Tong; Luo, Dan (Frontiers in Public Health, 2022)
Rapid social change has given rise to a general increase in psychological pressure, which has led to more and more Chinese people suffering from depression over the past 30 years. Depression was influenced not only by individual factors but also by social factors, such as economy, culture, politics, etc. These social factors were measured at the national, provincial, or community level. However, little literature reported the influence of province-level factors on the depression of Chinese. This study examined the effects of province-level and individual-level factors on depression of Chinese respondents aged 16-97 years. We conducted a multilevel analysis of the 2018 wave survey of the Chinese Family Panel Studies (CFPS), with 19,072 respondents nested within the 25 Chinese provinces. Data for province-level were extracted from the National Bureau of Statistics of China, including three predictors: gross regional product (GRP) per capita, expenditure for social security and employment (ESSE), and rural and urban household income inequality. Depression was measured with the eight-item short version of the Center for Epidemiologic Studies Depression Scale (CES-D8). The study found that respondents who were female, 30-59 years, divorced or widowed, less educated, rural residents, less body mass index (BMI), or had lower household income tended to report higher levels of depressive symptoms. After adjustment for individual-level features, a significant effect of provinces still survived. The respondents who lived in a province with higher GRP, higher ESSE, or smaller rural and urban household income inequality reported lower depressive symptoms. Our results demonstrated that individual features did not fully explain depression. Economic and social factors appeared to impact depression and have to be considered when the government planned for improved public depression. Meanwhile, our research also provided a suggestion for the government of some provinces to investigate and improve depression.